E2F1/SNHG7/miR-186-5p/MMP2 axis modulates the proliferation and migration of vascular endothelial cell in atherosclerosis - Zhang, Shengjie; Zhu, Xiaotong; Li, Guangping (Life sciences (1973), 2020)
Emerging literature illustrates critical roles of long noncoding RNAs (lncRNAs) in the progression of atherosclerosis. However, the biological functions and mechanism by which lncRNAs regulate the atherosclerosis remain unclear. Human umbilical vein endothelial cells (HUVECs) were treated with oxidative low-density lipoprotein (ox-LDL). RNA and protein levels were respectively measured using RT-qPCR and western blot. Molecular interaction was detected using luciferase reporter assay and chromatin immunoprecipitation (ChIP). Proliferation and migration were measured using CCK-8 and wound healing assay. Here, results unveiled that lncRNA SNHG7 was remarkedly up-regulated in ox-LDL exposed HUVECs. Gain and loss of function experiments showed that the SNHG7 repressed the proliferation and migration of HUVECs. Mechanistically, transcription factor E2F1 was found to target the promoter region of lncRNA SNHG7 and accelerated its expression. Moreover, miR-186-5p was found to bind with the 3′-UTR of SNHG7, meanwhile miR-186-5p also bound with the MMP2 mRNA 3′-UTR. In conclusion, these results show the essential roles of E2F1/SNHG7/miR-186-5p/MMP2 axis on the proliferation and migration of endothelial cells, providing a potential therapeutic target for atherosclerosis.